Shared decision making, preoperative expectations, and postoperative reality: differences in physician and patient predictions and ratings of knee surgery outcomes. - Rosenberger, Patricia H; Jokl, Peter; Cameron, Ann; Ickovics, Jeannette R (Arthroscopy : the journal of arthroscopic & related surgery : official publication of the Arthroscopy Association of North America and the International Arthroscopy Association, 2005)
The present study was performed to determine the extent to which physicians and patients rate preoperative and postoperative knee pain and function differently, and to determine whether physicians or patients more accurately predict postoperative knee pain and function.
Keywords: Anterior Cruciate Ligament; Athletic Injuries; Decision Making; Humans; Interviews as Topic; Knee Injuries; Knee Joint; Menisci, Tibial; Orthopedic Procedures; Pain Measurement; Pain, Postoperative; Patient Participation; Patient Satisfaction; Physician-Patient Relations; Treatment Outcome; United States; Workers' Compensation